Bruce Bronzan 40th Birthday Dinner Party at Doug and Gerre Jones Home - Watkins, Howard::::::::: (1987)
Clockwise: Table 1: Debbie Atkins, Dennis Atkins, ?, Mini Mott-Smitch, Bruce Bronzan, Linda Bronzan, Terry Easley, Marsha Easley, Elaine Long, Bud Long, and Tony Ross; Table 2: Larry Tunison, Harriet Tunison, Dr. Charles Gesserg, Doug Jones, ?, Dr. John Renisch, Betsy Blossom, John Blossom, Gerre Gurland-Jones.